Antibacterial Activity of Robusta Coffee (Coffea robusta) Husk Extract Against Streptococcus mutans and Lactobacillus acidophilus: In Vitro Study - Arlin R Kusumawardani; Andi M Machbub; Rendra C Prasetya; Nadie Fatimatuzzahro; Tantin Ermawati (Wolters Kluwer Medknow Publications, 2022)
Introduction: Caries is a tooth and oral illness caused by Streptococcus mutans and Lactobacillus acidophilus bacteria. The growth of caries-causing bacteria can be controlled by using 0.2% chlorhexidine mouthwash to control plaque, however long-term usage of 0.2% chlorhexidine causes negative effects. Natural components such as robusta coffee (Coffea robusta) husk, which possesses active compounds of polyphenols, flavonoids, alkaloids, tannins, and saponins as alternative antibacterials, can be used to reduce adverse effects. The aim of this research is to assess the antibacterial activity of robusta coffee husk extract against S. mutans and L. acidophilus. Materials and Methods: The robusta coffee husk was extracted using the maceration process with 96% ethanol as the solvent. Antibacterial test is conducted against S. mutans and L. acidophilus using disc diffusion method (Kirby-Baurer) with six treatment groups of extract concentration 250, 500, 750, 1000 mg/mL, positive control (0.2% chlorhexidine), and negative control (aquades steril). The zone of inhibition was measured in millimetres using a digital calliper (mm). The SPSS application was used to examine the calculation findings, which included the Shapiro-Wilk, Levene, One Way ANOVA, and Post Hoc LSD tests. Results: Robusta coffee husk extract at 250, 500, 750, and 1000 mg/mL doses shown bactericidal activity in S. mutans (radical zone) and bacteriostatic activity in L. acidophilus (irradical zone). Conclusion: Robusta coffee husk extract has an antibacterial activity against S. mutans and L. acidophilus. The highest inhibition zone was demonstrated by the 1000 mg/mL concentration of extract.